Are Islamic stock markets immune from contagion during the financial crisis? - Zhang, Hengchao; Mohamad, Azhar; Hamid, Zarinah (2021)
We assess the contagion effect of the global financial crisis (GFC) and the European debt crisis (EDC) on Islamic and conventional stock market indices of the US, GCC and Malaysia. We run the asymmetric dynamic conditional correlation GARCH specification on daily closing prices of relevant indices from 1 January 2006 through 31 December 2016. Our results show that the Malaysia Islamic stock market is exempted from the contagion effect of GFC and EDC when the shock stems from the US Islamic stock market. Investors in the US Islamic equity markets can create a safety net by reallocating some of their portfolios into Malaysia Islamic stock market, which appears to be more resilient. However, we do find a significant contagion influence between the US Islamic and GCC Islamic stock market, suggesting that the GCC Islamic stock market cannot provide an effective hedge for the US investors seeking a Shariah-compliant investment. Contagion effect generally is inconsistent and not significant for conventional stock markets of these three countries.